UTILIZATION OF GYPSUM POWDER WASTE AS A SUBSTITUTE FOR PART OF CEMENT IN POROUS CONCRETE COMPRESSIVE STRENGTH - AGA PRIATNA; YONAS PRIMA ARGA RUMBYARSO; GALI PRIBADI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2025)
Porous concrete is used in infrastructure projects that require water absorption, supporting green cities and sustainable development. Its composition differs from conventional concrete because it has minimal or no fine aggregates, thus forming pores. This study aims to compare the compressive strength of normal porous concrete with porous concrete in which some of the cement is replaced with gypsum board waste powder. Testing was conducted at 7, 14, and 28 days to determine the effect of waste on concrete strength development. Compressive strength testing of porous concrete with varying amounts of gypsum powder waste showed that at 0% composition, the results at 7 and 14 days met the SNI 1974: 2011 standard. However, at 5% and 10% composition, the results at 7 days only partially met the standard, while at 14 days they were below the minimum limit of 88%. This indicates a decrease in compressive strength performance as the percentage of gypsum waste increases.